The Origin of the Markan Passion-Sayings - Taylor, Vincent (New Testament studies, 1955)
My first words must be words of thanks for the great honour done to me in appointing me President of this Society for the year 1954-5 in succession to Professor Rudolf Bultmann. I also wish to express my deep regret that circumstances beyond my control prevent me from being present at Marburg to deliver the address in person.